Industrial Agglomeration and Industrial Policies: The Philippine Experience - Philippine Institute for Development Studies (PIDS) (Philippine Institute for Development Studies (PIDS), 2008)
In the relatively new body of ideas dubbed new economic geography and spatial economics, we find insights on the potentials of industrial agglomeration for regional and national economic development. This paper looked into the evolution of industrial development in the country as a means of elucidating the centripetal and centrifugal forces leading to agglomeration of firms and investments. A micro perspective was provided with the case study extended into the prime region in the country, Greater Manila Area. It was found that industrial agglomeration in the country takes the form of special economic zones and industry clusters, indicating that the government is taking the route toward regional dispersal of industries and the clustering strategy to spur industrial dynamism and competitiveness and consequently, regional and national economic development.
Keywords: 330; industrial agglomeration; industry clustering; trade and industry policy; special economic zones; Industriepolitik; Regionales Cluster; Philippinen; Manila